Ecosystem service measurement model for urban population clean water monitoring. Issue 1 (1st February 2022) - Samadi, S; Suhardjo, S; Munandar, A; Husen, A
Abstract: Clean Ecosystem service measurement model for urban population clean water monitoring Clean water as one of the ecosystem services and also a protected natural asset provides important information about the availability of natural resources for humans in response to the impacts of climate change and overall ecosystem health. The emergence of the COVID-19 pandemic which was exacerbated by the emergence of low-pressure areas for piped clean water services (PAM water) increasingly shows that if humans destroy biodiversity, it will have implications for other life support systems including clean water. This study identifies aspects of quantity, continuity, and quality (called 3K) of clean water from the piping system in the eastern part of DKI Jakarta, especially in areas with low pressure water supply. Through the Research and Development method, the aim of the study is to build a new model for measuring ecosystem services in monitoring clean water for residents in urban areas. Until the end of the first semester of 2020, the results of the study showed that it was true that there were areas with low pressure, but statistically it was not proven to significantly affect the emergence of complaints in terms of quantity, continuity, and quality of water supply to the population, so more in-depth parameters are needed. regarding the parameters of small water complaints (quantity), dead water (continuity), and piped clean water quality.